Prospects and development in the Malaysian herbal industry: an enlightening talk by Dr. Vijayan Ellappan / Siti Alwani Ariffin - Ariffin, Siti Alwani (Faculty of Pharmacy, 2024)
On July 3, 2024, an enlightening talk titled "Local Herbal Treasure: Prospects and Development in the Malaysian Herbal Industry" was held at DK 9, Faculty of Pharmacy, UiTM Puncak Alam as part of the Traditional and Complementary Medicine (T&CM) Collaborative Teaching. This insightful session, led by Dr. Vijayan Ellappan, a distinguished herbal medicine practitioner, attracted 65 participants, including students and lecturers. This two-hour talk, from 8:30 to 10:30 AM, aimed at providing comprehensive exposure to local herbs, their benefits, potential applications, and the broader industrial uses and developments in the Malaysian herbal sector.